Operational strategy optimisation of VRB energy storage systems considering the dynamic characteristics of VRB in active distribution networks - Jiazhi Lei; David Wenzhong Gao; Jinhong Liu (IET Renewable Power Generation, 2021)
Abstract Strategy optimisation of large‐scale battery energy storage system (BESS) operation in active distribution networks (ADNs) is an actively pursued research topic concerned by electric power researchers. This study proposes a dynamic programming method (DPM)‐based operational strategy optimisation of vanadium redox flow battery (VRB) ESSs for the comprehensive performance of ADNs considering the dynamic characteristics of VRB. The dynamic characteristics of VRB based on self‐discharge rate, dynamic efficiencies, maximum absorption power, cycle life and apparent power are reasonably proposed to construct the operational restrictions of ESSs. VRB is safely and reasonably operated with high cycle life and ideal states by these dynamic operational restrictions. And then, DPM is used to decompose the multivariate optimisation problem into several univariate optimisation problems. Finally, different case studies showed that the developed operation strategy of VRB ESSs can greatly improve both the economy and the voltage quality of ADNs. Also, the curtailment rate of renewable energy in ADNs is greatly reduced by about 50% and VRB ESSs can get a perfect optimisation associated with a higher utilisation rate of about 0.8 and an ameliorative average efficiency of about 0.753.